2015
DOI: 10.1016/j.jbusres.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The moderating influences on the relationship of corporate reputation with its antecedents and consequences: A meta-analytic review

Abstract: Through a meta-analytical approach, we test the antecedents and consequences of corporate reputation, examining specifically the moderating roles of three study variables: country of study, stakeholder group, and reputational measure. The study presents a comprehensive overview of three moderating factors for the relationship of corporate reputation with its antecedents and consequences in the literature from 101 quantitative studies. Our findings suggest that practitioners need to exercise considerable cautio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(198 citation statements)
references
References 123 publications
7
164
0
13
Order By: Relevance
“…For example, the Chinese office of Novel Insights was considered as a 'rising star' and 'number three' within the organisation, whereas the UK office was seen as one of the firm's 'Achilles heels' and near the bottom of the organisation's office hierarchy in terms of reputation. This is a significant insight because these findings go beyond the argument elsewhere in the literature that geographical context is important to study and affects stakeholder perceptions of companies (Bartikowksi et al, 2011;Soleimani et al, 2014;Ali et a., 2015). We extend this literature not only showing how the reputation of an organisational partnership varies both internally and externally by geography, but also why: namely, because of the distinct relationship that the individual has with the organisation.…”
Section: Geography and Corporate Reputationsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, the Chinese office of Novel Insights was considered as a 'rising star' and 'number three' within the organisation, whereas the UK office was seen as one of the firm's 'Achilles heels' and near the bottom of the organisation's office hierarchy in terms of reputation. This is a significant insight because these findings go beyond the argument elsewhere in the literature that geographical context is important to study and affects stakeholder perceptions of companies (Bartikowksi et al, 2011;Soleimani et al, 2014;Ali et a., 2015). We extend this literature not only showing how the reputation of an organisational partnership varies both internally and externally by geography, but also why: namely, because of the distinct relationship that the individual has with the organisation.…”
Section: Geography and Corporate Reputationsupporting
confidence: 60%
“…In all cases, the reputation became less superficial as employees became aware of the firm's core values and expertise as well as its weaknesses compared to its competitors. This is important theoretically because existing literature tends to theorise reputation at an organisational level, rather than at the individual level (Fombrun and Gardberg, 2000;Walsh et al, 2009;Ali et al, 2015). By changing the level of analysis, our findings show that an individual's regard for the organisation's reputation may strengthen as time passes, thereby 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Gotsi and Wilson, 2001).…”
Section: Multi-faceted Reputations Across Categoriesmentioning
confidence: 99%
“…To test these hypotheses, this study conducted a meta-analysis, an approach that has been shown to be useful where previous studies have yielded inconclusive results [50]. A meta-analysis has been successfully applied in several disciplines, including management (see [42,51,52]) and sustainability [53].…”
Section: Methodsmentioning
confidence: 99%
“…Aspects of accounting for goodwill and its impact on the results of managing enterprises are reflected in the works of scientists around the world. The study [3] presents a meta-analytical review of factors that have a deterrent effect on corporate reputation. This study is useful for Ukrainian enterprises because, having determined the list of negative factors, it is possible to limit their influence on the reputation of the enterprise than to stimulate development processes.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%